2020
DOI: 10.15421/2020_199
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic changes in pig organs, infected with the Aujeszkys disease

Abstract: The data on histological studies of organs of suckling piglets that died from Aujeszky's disease presented in the article. To study of the microscopic changes, organ and tissue samples were taken from 5 suckling pigs (aged 4 to 6 days old). In all piglets, the diagnosis was confirmed by polymerase chain reaction. For histological studies, tissue samples were taken from the following organs: lungs, stomach, intestines, liver, pancreas, kidneys, thymus, lymph nodes, spleen, brain and spinal cord. The studies est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
1
0
2
Order By: Relevance
“…However, it was found that the dosage form and manufacturing technology of drugs are also essential and their physical state, the properties of the constituent components, and the route of administration into the body (Pink et al, 2005;Mukherjee et al, 2016). The study of their toxic effects on biological objects is an intermediate stage in testing new chemical compounds (Bondarchuk et al, 2019;Orobchenko et al, 2020;Kovalenko et al, 2020). The research aim was to estimate the suggested innovative complex veterinary drugs.…”
Section: Effectiveness Of a Modern Antiparasitic Agentmentioning
confidence: 99%
“…However, it was found that the dosage form and manufacturing technology of drugs are also essential and their physical state, the properties of the constituent components, and the route of administration into the body (Pink et al, 2005;Mukherjee et al, 2016). The study of their toxic effects on biological objects is an intermediate stage in testing new chemical compounds (Bondarchuk et al, 2019;Orobchenko et al, 2020;Kovalenko et al, 2020). The research aim was to estimate the suggested innovative complex veterinary drugs.…”
Section: Effectiveness Of a Modern Antiparasitic Agentmentioning
confidence: 99%
“…У даний час фармацевтична галузь постійно працює над створенням ідеальних дезінфікуючих засобів, які б володіли широким спектром антимікробної дії у мінімальних концентраціях, не спричиняли формування стійкості у бактерій, були не токсичними, не корозійними, не алергенними, дешевими, тощо (Palii et al, 2020;Kovalenko et al, 2020). Для цього використовуються та поєднаються між собою дезінфікуючі субстанції із різних груп, дія яких направлена на пригнічення активності різних ферментних систем бактеріальної клітини та руйнування її структурних елементів (Augustin et al, 2004;Kovalenko et al, 2018).…”
Section: вступunclassified
“…Наявність мікробних біоплівок на поверхнях медичних інструментів, операційному обладнанні, протезах, катетерах, технологічних лініях у харчовій промисловості вважається чинником, який сприяє інфікуванню макроорганізму, забрудненню сировини та продукції (Hoque et al, 2015;Kukhtyn et al, 2017;Berhilevych et al, 2017). Тому використання біоцидів направлене на знищення планктонних і біоплівкових форм мікроорганізмів на різних поверхнях (Augustin et al, 2004;Kovalenko et al, 2018;Palii et al, 2020). Однак успішна боротьба з мікроорганізмами, які перебувають у біоплівках, можлива за умови застосування дезінфікуючих засобів, які руйнують екзополісахаридний матрикс і сприяють тіснішому контакту бактерій з біоцидом (Lequette et al, 2010).…”
Section: обговоренняunclassified